Using Human Factors Science to Improve Quality and Safety of Healthcare - Paul Bowie; Alia Al Baharnah; Rabab Alkutbe; Muhammad Mohsin Abid; Abdullah Almelaifi; Muhammad Hasan Abid (Global Journal on Quality and Safety in Healthcare)
Introduction The venous thromboembolism (VTE) risk screening forms were developed to allow for recording identified risk factors for VTE including thrombophilia, history of VTE, postpartum hemorrhage, and cesarean delivery, and documentation of specific actions taken to mitigate these risks and reduce complications due to VTE. Methods Compliance with hospital guidelines in assessing VTE risk and appropriate prescribing of thromboprophylaxis was evaluated prior to the introduction of VTE risk screening forms (March 2022). Efficacy of the new VTE risk screening forms was also assessed (April 2023). Patient discharge summaries and patient medical records including medication charts were used to review the documentation of VTE risk assessments and details of thromboprophylaxis prescribing. Results Of 74 postnatal patients, 37.8% had VTE risk assessment documented prior to the introduction of VTE risk screening forms. Of 37 patients identified to be at moderate to high risk of VTE requiring pharmacological prophylaxis, 70.3% (n = 26) were appropriately prescribed pharmacological prophylaxis. After the risk screening forms were introduced, a total of 67 antenatal, postnatal, and gynecologic patients were studied. Of these, 32.8% (n = 22) of patients had all required fields completed appropriately. When using the forms, 26.9% (n = 7) of postnatal and 88% (n = 22) of gynecological patients were rated as medium or high risk, and all received medical review within 24 hours. Pharmacological prophylaxis was indicated in 88% (n = 22) of gynecological, 43.8% (n = 7) of antenatal, and 38.5% (n = 10) of postnatal patients, and all were appropriately prescribed. Conclusion The guideline review and introduction of VTE risk screening forms was valuable to provide guidance in the risk assessment for VTE and to identify patients requiring prophylaxis.